Kolaborasi Model Pentahelix Dalam Pengembangan Desa Wisata Sei Gohong Kecamatan Bukit Batu Kota Palangka Raya - Philianto Dani Rahu; Suprayitno, Suprayitno (Journal Ilmu Sosial, Politik dan Pemerintahan, 2021)
Palangka Raya City has many tourist attraction locations related to natural tourism, cultural tourism, religious tourism that can be developed, one of which is the Sei Gohong Tourism Village. So that with the management, construction of facilities and infrastructure as well as increased productivity, innovation, creativity, will increase the Regional Original Income (PAD) of Palangka Raya City. This study aims to describe and analyze how the optimization of the Pentahelix Model Collaboration in the Development of Sei Gohong Tourism Village, Bukit Batu District, Palangka Raya City. This study uses a qualitative approach because according to researchers’ qualitative research methods are more suitable for exploring and describing in depth the problems to be raisedregarding the Pentahelix Collaboration Model in the Development of Sei Gohong Tourism Village, Bukit Batu District, Palangka Raya City. To see optimal collaboration, it can be measured by theory (Gray, 1989) which includes: (1) Interdependence, (2) Constructive Unification of Thought to Achieve Solutions, (3) Joint Ownership of Decisions, (4) Joint Responsibilities. The results showed that the Pentahelix Model Collaboration in the Development of Sei Gohong Tourism Village, Bukit Batu District, Palangka Raya City is stillnot optimal. This can be seen from the level of cooperation between Pentahelix stakeholders which is still not running optimally, there is no dependence between stakeholders and other stakeholders, the lack of constructive unification ofthought to reach a solution because the meeting rate is very low and unscheduled, so that for joint decisions all actors ( Joint ownership of decisions in determining Musrenbang policies is not entirely based on mutual agreement, besides joint responsibility so far there is still no binding law based on cooperation (MOU). Suggestions for increasing collaboration on the importance of goodcommunication and conducting regular meetings involving various Pentahelix stakeholder actors to unite the same vision and mission by holding events, as well as the formation of regulations as one of the supporting factors for the creation of the Pentahelix Model Collaboration in the Development of Sei Gohong Tourism Village, District Bukit Batu City of Palangka Raya